Analysis Of The Difference In Broiler Chicken Sales Volume Before And After Halal Certification (Case Study of Alhijrah Chicken Slaughterhouse in Kendari) - Ariana, Jihan; Fyka, Samsul Alam; Sudarmo, Hadi (International journal of technology and education research, 2025)
This study aims to analyze the difference in the volume of broiler chicken sales before and after halal certification at the Alhijrah Kendari Chicken Slaughterhouse (RPA). Halal certification is a crucial factor that influences consumer trust and purchasing decisions, especially in a predominantly Muslim community. The research employs a quantitative approach using paired t-test analysis to compare the sales data of broiler chickens before and after certification was obtained. The findings indicate a significant increase in the sales volume of broiler chickens following the halal certification, with a notable surge of 2-3 times during major religious holidays, such as Eid. This increase highlights the positive impact of halal certification on consumer behavior, as it assures them of the product's quality and compliance with religious standards. The results of this study provide valuable insights for business owners and stakeholders in the poultry industry, emphasizing the potential benefits of obtaining halal certification to boost sales and consumer trust in the market